1980
DOI: 10.1051/rnd:19800104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting on blood composition and nitrogen losses in the adult sheep depending on previous diet and body weight

Abstract: Summary. In order to study the profiles of blood composition and nitrogen losses during fasting, groups of adult sheep that had previously received diets with variable intake levels were fasted during 8-day periods. A decrease in blood ketone concentration was observed during the first day, followed by a strong increase after 36 to 48 hrs. After The role of the ketone bodies and the protein reserves in meeting energy needs and in maintaining glycemia during fasting have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
4
2
1
Order By: Relevance
“…This pattern in the ad libitum fed sheep shows that increasing FFA concentration was associated with stable and high body fat content and a decline in food intake. In previous papers (Bouchat et a/., 1980 ;1981) we confirmed the findings of other authors (GOnzel and Giesecke, 1974 ;Thompson et al, 1975 ;Thye et al, 1970), demonstrating that fasting induces a rapid increase in the FFA concentration from the first day of fasting and that the concentration tends to stabilize after 5-6 days of fasting. Moreover, this concentration is influenced by the nature and the level of food offered (Bouchat et al, 1981).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This pattern in the ad libitum fed sheep shows that increasing FFA concentration was associated with stable and high body fat content and a decline in food intake. In previous papers (Bouchat et a/., 1980 ;1981) we confirmed the findings of other authors (GOnzel and Giesecke, 1974 ;Thompson et al, 1975 ;Thye et al, 1970), demonstrating that fasting induces a rapid increase in the FFA concentration from the first day of fasting and that the concentration tends to stabilize after 5-6 days of fasting. Moreover, this concentration is influenced by the nature and the level of food offered (Bouchat et al, 1981).…”
Section: Discussionsupporting
confidence: 80%
“…The fatty acid composition of the lipid fractions was comparable with that obtained previously (Bouchat et al, 1980(Bouchat et al, , 1981 and analogous results were reported by Garton (1960) and Lindsay and Leat (1977).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations